Synthetic Chemistry of Nanomaterials - Qiao, S.; Liu, Jian; Max Lu, G. (Elsevier, 2017)
© 2017 Elsevier B.V. All rights reserved. The preparation and application of nanomaterials have made tremendous achievements in recent decades because of the improvement of synthetic chemistry at the nanoscale. These developments have led to various nanomaterials, which have brought evolution in relevant fields such as catalysis, biomedicine, photonics, etc. By developing synthetic chemistry, the design of nanostructures with tunable geometries, tailored sizes, and activities can be achieved through different synthetic strategies. This chapter gives a systematical introduction to the fabrication of nanomaterials in two sections. The first section represents a detailed review of major synthetic routines in two categories: top-down and bottom-up methods. It provides an overview of nanofabrication techniques as well as referential examples of some particulars. The second section highlights the studies of several specific nanostructures including nanocrystals, nanowires, and hollow/core-shell nanostructures. In particular, the superior properties and functions of these nanomaterials are surveyed with the intention of providing guidance on future fabrication of nanomaterials.